Family Takaful subscription behavior : motivational factors for Generation-Y - Muhammad Syafiq Ismail (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Family Takaful provides an alternative for Muslim in Malaysia to enjoy similar protection as conventional insurance that comply with Shariah requirements. Half of the Generation-Y (Gen-Y) in Malaysia does not have any protection coverage, thus prompt the study of what motivates Gen-Y to subscribe to Family Takaful plan. Greater Kuala Lumpur was selected to reflect economic capacity of respondents. Samples of 228 questionnaires were distributed to identify Gen-Y's motivating factors and determine their order of importance. Descriptive data analysis method and Pearson's Chi-square test were used to analyze data collected. Family Takaful industry's practice and regulation, Family Takaful products, individual's financial position and religious factors were the four motivational factors identified. In order of importance, Gen-Y in Greater-KL believes religious factors to be the most important factor they consider in subscribing to Family Takaful plan, while Family Takaful industry's practice and regulation was identified to be the least important factor in making subscription decision. Cross tabulation analysis of each factor shows repetitive significance between marital status, employment, monthly earning, and subscription position of respondents with industry's stability, public trust, pricing mechanism, financial incentive, financial commitment, and fulfillment of Shariah objectives. Gen-Y's acceptance to government support provides an opportunity for government to increase awareness on the importance of Family Takaful. Gen-Y satisfaction with current product structure allows Family Takaful industry to focus on improving their service and operation. Transparency of Family Takaful industry's adherence to Shariah principles will boost Gen-Y's confidence and trust to the industry. Future research could observe the consumption psychology of Gen-Y in Greater-KL, specifically on the preference of individual and collective benefits in making consumption decision. Furthermore, expansion of this study to other geographical area in Malaysia provides more comprehensive findings on motivational factors of Gen-Y in subscribing to Family Takaful across Malaysia.